Management Analysis and Availability of Practical Equipment at the Machining Workshop of SMK Negeri 2 Palembang - Saputra, Aria; Harlin, Harlin (Journal of English Language and Education, 2025)
The background of this research departs from the problem of limited number of practical equipment, suboptimal maintenance, and budget limitations that have an impact on the smooth running of learning activities. This study aims to analyze the management and availability of practical equipment in the machining workshop of SMK Negeri 2 Palembang. The research method used is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study show that the management of practical equipment in the machining workshop has implemented a clear task sharing system between toolman and maintenance repair (MR) officers, so that the equipment can be used optimally. However, the amount of equipment available is not yet proportional to the number of students, so practice must be done alternately through scheduling. The conclusion of this study is that budget constraints, length of procurement process, and limited number of equipment are the main obstacles, but can be minimized through more effective usage and maintenance management strategies. This research is expected to be an input for schools in improving the effectiveness of workshop management and the provision of practical equipment to support the achievement of curriculum goals.